Penerapan Knowledge Management di SMK Diponegoro Depok - Pratama, Yoga Anjas (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2018)
This article discusses about knowledge management and its application in smk diponegoro depok. The concept of knowledge management is the concept of resource management and information technology owned. This concept is based on resource theory (resource-based theory) and knowledge based theory. In knowledge management educational institutions are applied in the form of improvement and utilization of resources and techonology of communication and information as knowledge assets in increasing competitive advantage. knowledge management in SMK Diponegoro Depok applied in the form of improvement and utilization of knowledge of educator, communication media and information technology, and knowledge sharing. From the mini research conducted in SMK Diponegoro Depok, found the following things: (1)  Has done a enhancement and resource utilization (2) Existence implementation of knowledge management (3) Doing a breakthrough in improving the quality of educators and learners (4) Smk diponegoro able to see great opportunities from the culture of information dissemination (5) The use of communication media and information technology is less significant in SMK Diponegoro Depok.